1999
DOI: 10.1039/a903185e
|View full text |Cite
|
Sign up to set email alerts
|

An EPR study of Cd2+ incorporation in vaterite

Abstract: 13C-vaterite, the unstable calcium carbonate polymorph, doped with Cd2`was c-irradiated and the stable paramagnetic centres were studied using electron paramagnetic resonance (EPR) spectroscopy. The 13C isotope has nuclear spin (I \ 1/2) and as a consequence hyperÐne interaction with the unpaired electron occurs. This revealed all paramagnetic centres of carbonate origin, i.e. and free radicals. Two ~CO 3 ~~CO 2 paramagnetic centres induced by cadmium doped to vaterite, one characterized by and the other g a \… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Therefore, the signals in Figure c were not derived from MgO but the CO 2 species adsorbed on MgO. It was reported that g = 1.998, 2002 and g = 2.007, 2.011, 2.022 are assigned to a CO 2 - radical and a CO 3 - radical, respectively. Our results are also supported by this assignment. In our case, the signals of the CO 2 - radical and the CO 3 - radical remained after 1 h although the light illumination was stopped.…”
Section: Resultssupporting
confidence: 80%
“…Therefore, the signals in Figure c were not derived from MgO but the CO 2 species adsorbed on MgO. It was reported that g = 1.998, 2002 and g = 2.007, 2.011, 2.022 are assigned to a CO 2 - radical and a CO 3 - radical, respectively. Our results are also supported by this assignment. In our case, the signals of the CO 2 - radical and the CO 3 - radical remained after 1 h although the light illumination was stopped.…”
Section: Resultssupporting
confidence: 80%
“…16 Stabilization of the vaterite form of CaCO 3 can be acheived via presence of impurities of inorgainc or orgainc materials. 17,18 To stablize the vaterite phase, several research groups used organic impurites such as ovalbumin, 18 polypeptide, 19 double hydrophilic block copolymers, 20 and anionic starburst dendrimer. 21 Cai et al embedded gold nanoparticles (NPs) into the pores of CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its industrial and commercial potential, there is a large body of literature that shows vaterite can be stabilized (often temporarily) in the presence of various different ions or organic and inorganic additives under widely differing experimental conditions, most of which are concerned with in vitro formation (e.g. Wray & Daniels 1957;Nassrallah-Aboukais et al 1998;Nothig-Laslo & Brecvić 1999;Han et al 2006;Nebel & Epple 2008;Wang et al 2009;Fernandez-Daz 2010;Gomez-Morales et al 2010), or as a post-formation coating (Vogel et al 2009). The origin of these stabilisation effects likely lies in the fact that vaterite, aragonite and calcite all have very similar values for their free energy (0.5-3 kJ/mol differences; Plummer & Busenberg 1982;Wolf et al 1996Wolf et al , 2000Baitalow et al 1998).…”
Section: Formation Of Vateritementioning
confidence: 99%
“…Wray & Daniels 1957;Nassrallah-Aboukais et al 1998;Nothig-Laslo & Brecvić 1999;Han et al 2006;Nebel & Epple 2008;Fernandez-Daz 2010;Gomez-Morales et al 2010), or as a post-formation coating (Vogel et al 2009). The origin of these stabilisation effects likely lies in the fact that vaterite, aragonite and calcite all have very similar values for their free energy (0.5-3 kJ/mol differences; Plummer & Busenberg 1982;Wolf et al 1996Wolf et al , 2000Baitalow et al 1998).…”
Section: Formation Of Vateritementioning
confidence: 99%